2004
DOI: 10.1002/bjs.4635
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the development of popliteal cysts

Abstract: Popliteal cysts are relatively common in patients over 50 years old with a painful knee or with signs and symptoms of DVT. They form in the posteromedial popliteal fossa because the synovial capsule does not provide anatomical support in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…Intervention can be surgical or conservative, depending on whether there is precipitating knee injury ultimately responsible for the development of the cyst. 8,41 Because rupture of the cyst may lead to the development of a critical compartment syndrome, patients with an elevated risk to develop venous thrombosis and pulmonary embolism should be carefully monitored because their management and treatment is informed by their potential to bleed into a synovial cyst. A complete differential diagnosis for pseudothrombophlebitic syndrome of the lower limb that includes a Baker cyst should involve venous duplex scanning and ultrasound imaging to rule out thrombosis and avoid unnecessary anticoagulation and potential bleeding into the cyst.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention can be surgical or conservative, depending on whether there is precipitating knee injury ultimately responsible for the development of the cyst. 8,41 Because rupture of the cyst may lead to the development of a critical compartment syndrome, patients with an elevated risk to develop venous thrombosis and pulmonary embolism should be carefully monitored because their management and treatment is informed by their potential to bleed into a synovial cyst. A complete differential diagnosis for pseudothrombophlebitic syndrome of the lower limb that includes a Baker cyst should involve venous duplex scanning and ultrasound imaging to rule out thrombosis and avoid unnecessary anticoagulation and potential bleeding into the cyst.…”
Section: Discussionmentioning
confidence: 99%
“…A 2004 prospective study designed to investigate the etiology of this cyst concluded that a popliteal cyst usually develops in the posteromedial popliteal fossa due to lack of anatomic support in this area of the synovial capsule. 8 The accumulation of fluid within the bursa in this medial anatomic location within the knee typically spares the posterolaterally located neurovascular bundle.…”
mentioning
confidence: 99%
“…The pathogenesis of synovial cyst of knee joint is explained by the presence of a communication between the joint and the bursa, continuous unidirectional flow via the valvular mechanism and unequal pressure between the joint and bursa during various knee movements [3][4][5]. Addressing these factors during the operative treatment of synovial cyst is important to prevent recurrence [12].…”
Section: Discussionmentioning
confidence: 99%
“…1 They can occur due to intraarticular pathology, including meniscal and anterior cruciate ligament tears, chondral lesions, and synovitis. 2 The underlying or associated intra-articular pathology must be addressed to prevent recurrence of the cyst.Surgical removal of popliteal cysts is indicated in rare cases when the cyst remains symptomatic despite treatment of intra-articular pathology or if no underlying cause is found. Historically, open surgical excision has been performed through a posterior approach or posteromedial approach.…”
mentioning
confidence: 99%
“…1 They can occur due to intraarticular pathology, including meniscal and anterior cruciate ligament tears, chondral lesions, and synovitis. 2 The underlying or associated intra-articular pathology must be addressed to prevent recurrence of the cyst.…”
mentioning
confidence: 99%